LEXICO-GRAMMATICAL POSSIBILITIES OF CASES IN THE RUSSIAN LANGUAGE (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The category of case combines morphological forms that serve as a means of connecting words in the Russian language. Case as a multifaceted phenomenon expresses semantic and syntactic relations. That is, this category also gives the combination a certain meaning within its scope. Each member of the category has a different meaning in phrases. If the syntactic feature associated with the connection of words serves to generalize phrases, then the semantic difference contributes to their separation.